Exploring housing market and urban densification during COVID-19 in Turkey - Moynul Ahsan; Cihan Sadak (Journal of Urban Management, 2021)
The paper explores the housing market, urban densification, and government policy interventions due to COVID-19 in Turkey. From 1980 to 2019, the share of urban population in Turkey increased from 43.78% to 75.14% (UN DESA, 2018) and simultaneously the housing production has been increased more than 30% at the same period and it has planned to build or reconstruct about 13 million housing units including 1 million housing units per year from 2020 (Housing Development Administration of Turkey, 2020). However, COVID-19 has radically changed Turkey's real estate market, more specifically, housing market. Based on secondary data and information, the study has found that there has been a sharp decrease occurred during the month of April and May in 2020 due to curfew and other related COVID-19 controlled measures. After government interventions such as lowering interest rates in public banks, online land registry applications, government stimulus packages etc. a sharp increase happened from June and the third quarter of 2020; even after out looking 10 lowest densely populated provinces, 10 highest densely populated provinces in Turkey and districts in Istanbul. Focusing impact on the housing market in three different quarters (Q1, Q2 and Q3) of 2020 in the studied areas, it has found that there is no significant relationship between housing sales with respect to population density but government policy intervention during COVID-19 plays a very significant role in increasing housing demand.
Keywords: 710; Housing market; Urban densification; Real estate; COVID-19; Government policy intervention